Clinical Practice Guidelines for Diagnosis and Non-Surgical Treatment of Primary Frozen Shoulder - Byung Chan Lee; Beom Suk Kim; Byeong-Ju Lee; Chang-Won Moon; Chul-Hyun Park; Dong Hwan Kim; Dong Hwan Yun; Donghwi Park; Doo Young Kim; Du Hwan Kim; Gi-Wook Kim; Hyun Jung Kim; et al. (Annals of Rehabilitation Medicine)
Objective Primary frozen shoulder causes significant pain and progressively restricts shoulder movements. Diagnosis is primarily clinically based on patient history and physical examination. Management is mainly non-invasive owing to its self-limiting clinical course. However, clinical practice guidelines for frozen shoulder have not yet been developed in Korea. The developed guidelines aim to provide evidence-based recommendations for the diagnosis and treatment of frozen shoulder. Methods A guideline development committee reviewed the literature from four databases (PubMed, Embase, Cochrane Library, and KMbase). Using the PICO (Population, Intervention, Comparator, and Outcome) framework, the committee formulated two backgrounds and 16 key questions to address common clinical concerns. Recommendations were made using the Grading of Recommendations, Assessment, Development, and Evaluation framework. Results Diabetes, thyroid disease, and dyslipidemia significantly increase the risk of developing a frozen shoulder. Although frozen shoulder is often self-limiting, some patients may experience long-term disabilities. Ultrasound and magnetic resonance imaging should be used as adjunctive tools alongside clinical diagnosis, and not as independent diagnostic methods. Noninvasive approaches, such as medications, physical modalities, exercises, electrical stimulation, and manual therapy, may reduce pain and improve shoulder function. Other noninvasive interventions have limited evidence, and their application should be based on clinical judgment. Intra-articular steroid injections are recommended for treatment, and physiotherapy or hydrodilatation with steroid injections can also be beneficial. Conclusion These guidelines provide evidence-based recommendations for diagnosing and treating primary frozen shoulder.